Gemifloxacin Is Effective in Experimental Pneumococcal Meningitis - Smirnov, A. (American Society for Microbiology, 2000)
In a rabbit model of Streptococcus pneumoniae meningitis, 5 mg of gemifloxacin mesylate (SB-265805) per kg/h reduced the bacterial titers in cerebrospinal fluid (CSF) almost as rapidly as 10 mg of ceftriaxone per kg/h (Δlog CFU/ml/h ± standard deviation [SD], −0.25 ± 0.09 versus −0.38 ± 0.11; serum and CSF concentrations of gemifloxacin were 2.1 ± 1.4 mg/liter and 0.59 ± 0.38 mg/liter, respectively, at 24 h). Coadministration of 1 mg of dexamethasone per kg did not affect gemifloxacin serum and CSF levels (2.7 ± 1.4 mg/liter and 0.75 ± 0.34 mg/liter, respectively, at 24 h) or activity (Δlog CFU/ml/h ± SD, −0.26 ± 0.11).